2020
DOI: 10.3389/fpsyt.2020.00141
|View full text |Cite
|
Sign up to set email alerts
|

Differential Regulation of DNA Methylation at the CRMP2 Promoter Region Between the Hippocampus and Prefrontal Cortex in a CUMS Depression Model

Abstract: Current evidence supports the idea that neural plasticity is a potential cause of depression. Abundant studies indicate that CRMP2 has important roles in neural plasticity. Moreover, CRMP2 may contribute to the etiology of depression. However, the regulatory mechanisms underlying the role of CRMP2 remain unclear. DNA methylation alteration is generally acknowledged to be involved in the development of depression. The aim of this study was to explore the relationship between the expression and DNA methylation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 57 publications
0
13
0
Order By: Relevance
“…This indicates that the changes in CRMP2 expression in the hippocampus and prefrontal cortex are related to the pathogenesis of depression. In addition, the results also show regional differences in the regulation of DNA methylation in the CRMP2 promoter between the hippocampus and the prefrontal cortex during the development of depression (Xiang et al, 2020). DNA methylation is a dynamic tissue-specific event that may play an important role in the persistent and recurrent nature of depression.…”
Section: Chronic Unpredictable Mild Stress Affects Methylationmentioning
confidence: 70%
“…This indicates that the changes in CRMP2 expression in the hippocampus and prefrontal cortex are related to the pathogenesis of depression. In addition, the results also show regional differences in the regulation of DNA methylation in the CRMP2 promoter between the hippocampus and the prefrontal cortex during the development of depression (Xiang et al, 2020). DNA methylation is a dynamic tissue-specific event that may play an important role in the persistent and recurrent nature of depression.…”
Section: Chronic Unpredictable Mild Stress Affects Methylationmentioning
confidence: 70%
“…CRMP2 has been proposed to be a candidate gene for the treatment of depression. In our previous study, the results showed a reduction in CRMP2 expression in the hippocampus of stressed rats, which may correlate with a significant increase in the DNA methylation levels of the CRMP2 promoter region (Xiang et al, 2020). Moreover, several studies suggested the important role of DNMTs in regulating depressive-like behaviors (Ignácio et al, 2017;Shen et al, 2019).…”
Section: Introductionmentioning
confidence: 82%
“…A video camera was configured above the field to monitor the locomotor activities of rats, including the number of square crossings, the number of rearing, and the number of grooming events within 5 min. The fewer the number of walk grids, the lesser the number of standing up, and the more the number of grooming, the more nervous the rats were 18 . The field was cleaned with alcohol for each test.…”
Section: Methodsmentioning
confidence: 99%
“…The fewer the number of walk grids, the lesser the number of standing up, and the more the number of grooming, the more nervous the rats were. 18 The field was cleaned with alcohol for each test. The final data were analyzed using a video capture master (VideoMot2, TSE Company, Germany).…”
Section: Open Field Test (Oft)mentioning
confidence: 99%